PERUMUSAN STRATEGI PENGEMBANGAN BISNIS DAUR ULANG LOGAM ALUMINIUM - Bagaskara, Mohammad Zoga; Moko, Wahdiyat (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Business developments in modern era have occurred in all categories of companies. The current fierce competition between companies is related to the growth of production volumes with sustaining attention to product quality will at least maintains the achieved selling figures. Various methods have been used to meet the goal, e.g. product planning, material procurement, promotion, price setting, and development of product required and desired by the market. The objective of this research is to identify the appropriate strategy to be applied by PT. Barokah Subur Jaya using strategy formulation approach. The data of this descriptive qualitative study was harvested through interviews and documentation in the research site, i.e. an aluminum recycling company. This study finds that PT. Barokah Subur Jaya need to apply the hold-and-maintain strategy.